Economic Vulnerability of Fishermen in South Garut to Weather Changes and Market Prices - Anggun Sulistia Ardani; Denia Multi Ramadhani; Nadya Amalia Fitriani; Sri Damayanti (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2026)
The economic vulnerability of fishermen in South Garut is a critical issue, influenced by unpredictable weather changes and fluctuations in market prices for their catch. These conditions directly impact fishermen's income and welfare, leading to prolonged economic uncertainty. The urgency of this research lies in the need for a deeper understanding of the factors influencing this vulnerability in order to formulate appropriate strategies to improve fishermen's economic resilience. This study aims to analyze the forms of economic vulnerability of fishermen and their causal factors in the South Garut region. The research method used is a qualitative approach with a case study method. Data were collected through in-depth interviews with fishermen, field observations, and analysis of related documents. Data analysis techniques were carried out descriptively through data reduction, data presentation, and drawing conclusions. The results show that fishermen's economic vulnerability is influenced by high dependence on natural conditions, limited access to technology and weather information, and unstable market price fluctuations. Furthermore, minimal institutional support and access to capital also exacerbate these conditions. This study recommends increasing access to weather information, strengthening fishermen's institutions, and implementing price stabilization policies to improve fishermen's welfare.